Legal Policy of Halal Products for the Development of Small and Micro Enterprises after the Enactment of Government Regulation in Lieu of Law No. 2 of 2022 on the Job Creation - Muin, Fatkhul; Tahir, Palmawati (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2023)
This study aims to examine the legal policy on halal products for micro, small, and medium enterprises (MSMEs) after the enactment of Government Regulations in lieu of Law No. 2 of 2022 concerning Job Creation. To meet the demand for halal products, government policy is needed to simplify the halal product submission system while maintaining its production by MSMEs in Indonesia. Based on data from the Indonesian Statistics Agency, Indonesia is a Muslim country with 237.53 million Muslims, accounting for 86.9% of the total population. This indicates a significant need for halal products. MSMEs are one of the sources of halal products; hence, the government needs to enact laws that facilitate their production procedures. Objectively, the requirement to have halal certification, as mentioned in Article 4A of Government Regulation in Lieu of Law No. 2 of 2022 concerning Job Creation, is based on halal declarations from MSME actors. These actors make halal declarations based on the guidelines set by the Halal Product Guarantee Agency (BPJPH). The ratification of this regulation aims to strengthen MSMEs and support the increase in halal products. Therefore, a legal approach based on primary legal materials related to legislation and secondary legal materials based on documents that support this study was adopted. In addition, data from the Ministry of Cooperation, Micro, Small, and Medium Enterprises reveal that there are 8.71 million MSMEs in Indonesia. This potential needs to be facilitated by policies to simplify the production of halal products with a measurable process based on statutory provisions.